Security and privacy challenges of big data adoption: A case study in the telecommunications industry - Anawar, Syarulnaziah; Selamat, Siti Rahayu; Othman, Nur Fadzilah; Harum, Norharyati; Ayop, Zakiah (Malaysian Communications and Multimedia Commission, 2023)
The telecommunications industry is the most appropriate industry to observe big data trends as this industry not only has the most capable infrastructure for big data collection, but also needs to utilise it extensively in the context of location services it provides to individuals. However, the adoption of big data in telecommunications services also raises important security and privacy challenges. This study focuses on investigating the security and privacy challenges for both data users and data subjects in telecommunications services and examines codes of practices and standards to address the privacy and security challenges. The proposed study is conducted using mixed-methodology, qualitative and quantitative methodology, where each phase is conducted concurrently and independently of each other. From the perspectives of data users, it could be concluded that data management, data privacy, data compliance, and regulatory orchestration challenges are the most pressing concerns in big data adoption. From the perspectives of the data subject, the findings indicate that only the error variable has a direct effect on big data adoption, which is partially mediated by perceived trust and perceived risk. Among the four variables of security and privacy concerns, the improper access variable has a significantly higher effect on perceived trust. Similarly, the collection variable has a significantly higher effect on perceived risk among the four variables. Finally, the findings show that telecommunications users' awareness of data privacy regulations greatly impacts big data adoption. The contributions of the proposed study are two-fold: (1) to help identify the perceived risk implications of the information collected, stored, shared, and managed in big data, and assess reasonable mitigation strategies in the context of data sharing for big data purposes; and (2) to serve as recommendations for the developers and decision-makers to design a secure and fully ethically compliant big data solution in the telecommunications industry.